A comparison of human and porcine acellular dermal tissues in the subcutaneous space of a rat model - Hoyama, Erika [UNESP]; Schellini, Silvana Artioli [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Rossa, Romualdo; Padovani, Carlos Roberto [UNESP] (Taylor & Francis, 2005)
The study compared the host response to a human and a porcine acellular dermal tissue implanted in the subcutaneous space of a rat model. The human and porcine acellular grafts were surgically implanted in the subcutaneous tissue of rats (5 rats/group) and the materials were evaluated at 7, 15, 30, 60 and 180 postoperative days (PO). The histological immune response was quantified using a digital image analysis system, which evaluated the number of vessels present in the implants and in the surrounding soft tissue, the area of inflammatory cell infiltration in the grafts, the width of the capsular formation present around the tissues and the area of implants absorbed. The data were submitted to statistical analysis. Light microscopy showed mononuclear cellular infiltration, the presence of a capsular formation surrounding the grafts and the presence of vacuolar structures (optically empty spaces) inside the implants. The image analysis comparing both materials showed significant inflammatory cells in the human graft at 15 and 30 PO, thicker capsular formation in the porcine tissue at 60 PO, increased number of vessels inside the implants and in the surrounding tissues in the porcine graft and a similar absorption pattern in both materials at 180 PO. The histological findings showed that both tissues were well-tolerated when implanted in the subcutaneous tissue of rats, allowing us to consider the porcine acellular dermal graft as a provisional alternative material for reconstructive plastic surgery. Copyright © 2005 Taylor & Francis LLC.
Keywords: Acellular dermal tissue; Biomaterials; Host vs. Graft response; Human tissue; Porcine tissue; Rats; Reconstructive plastic surgery; absorption; animal experiment; animal tissue; blood vessel; cell infiltration; cell vacuole; conference paper; controlled study; dermis; evaluation; histology; human; human experiment; human tissue; image analysis; immune response; implant; implantation; inflammatory cell; male; microscopy; mononuclear cell; nonhuman; plastic surgery; postoperative period; quantitative analysis; rat; skin graft; skin transplantation; soft tissue; species comparison; statistical analysis; subcutaneous tissue; swine; Analysis of Variance; Animals; Graft Survival; Humans; Inflammation; Male; Models, Animal; Skin; Skin Transplantation; Statistics, Nonparametric; Subcutaneous Tissue; Swine